2012
DOI: 10.1111/j.1440-172x.2012.02067.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the online nursing evidence‐based information resources for evidence‐based nursing study in China

Abstract: At present Chinese nurses could not get the up-to-date and high-quality evidences efficiently and conveniently due to language barrier and other practical difficulties. This program built a Chinese website of integrated evidence-based network information resources for EBN studies. Researchers hope to provide practical guidance and advice for nurses in non-English-speaking countries..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…With English being the international language of science [ 42 ], the majority of nursing research is published in English; however, less than 1 % of people in China are able to fluently understand it [ 43 ]. Translating evidence-based guidelines into Chinese could help overcome language obstacles to accessing research evidence in China [ 4 , 44 ]. In Canada, the Registered Nurses’ Association of Ontario (RNAO) has produced evidence-based guidelines for nursing care that are freely available on their website ( http://rnao.ca/bpg/language ), and a number are being translated into Chinese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With English being the international language of science [ 42 ], the majority of nursing research is published in English; however, less than 1 % of people in China are able to fluently understand it [ 43 ]. Translating evidence-based guidelines into Chinese could help overcome language obstacles to accessing research evidence in China [ 4 , 44 ]. In Canada, the Registered Nurses’ Association of Ontario (RNAO) has produced evidence-based guidelines for nursing care that are freely available on their website ( http://rnao.ca/bpg/language ), and a number are being translated into Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…However, gaps exist between recommendations for EBP and the actual care nurses provide in practice [ 2 , 3 ]. A range of barriers has been identified, however, and while factors that influence EBP have been extensively explored by researchers in many countries, this has predominantly taken place in Western cultures; little information exists about EBP in China [ 4 , 5 ]. As a relatively new concept, a recent scoping review ( n = 95 articles) found barriers not commonly documented in western countries [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sufficient resources must be provided to reviewers to learn methods of SRs/MAs as well as guidelines for reporting and quality assessment, and the collaboration with statisticians and librarians is also encouraged. Referring to the language problem, a website of integrated evidence‐based network information resources for EBHC studies was established by Fudan University (He & Hu, ). In 2015, the first Joanna Briggs Collaboration Centre for TCM EBHC was set up in Beijing University of Chinese Medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The Journal also achieves its goal of internationality, although notably dominated by English‐speaking nations. This is not surprising given that English is considered the ‘language of health science’ (da Silva et al, ) and English as a second language is a recognized barrier in dissemination for international nursing scholars (He & Hu, ). The Journal also aims to inform practitioners and researchers in nursing management and leadership; explore and debate current issues in nursing management and leadership; assess the evidence for current practice; develop best practice in nursing management and leadership; examine the impact of policy developments; and address issues in governance.…”
Section: An Outline Of Patterns and Trends In Papers Published The Jomentioning
confidence: 99%